Analisis puisi ‘Aku Merindukanmu’ karya Mim Yudiarto dengan pendekatan semiotika - Neisyiah, Devana Nur (Maliki Interdisciplinary Journal, 2024)
The purpose of this article is to discuss hidden meanings in poetic texts through discussion and exposure to semiotics. The method used is descriptive qualitative with poetry as the research data object. The results of the research show that Mim Yudiarto’s poem entitled "Aku Merindukanmu" has strong symbols that can form meaning. The concept of deep longing of various colors towards the figure of the mother is the dominant theme in this poem. Therefore, the aim of this research is to open research that utilizes semiotic theory to study poetry and other literary works.